Work Motivation as a Mediating Variable between Human Resources Competence and Organizational Climate against Job Satisfaction at the Yapen Islands Resort Police - Almon Julius Marpaung (Britain International for Academic Research (BIAR) Publisher, 2021)
This research was conducted to analyze the influence of HR competence and organizational climate on work motivation, the influence of HR competence, organizational climate, and work motivation on job satisfaction, and work motivation as a mediation for the influence of HR competence and organizational climate on job satisfaction. Descriptive research method with a quantitative approach to causality was used. Simple random sampling technique and Slovin formula were used to determine the number of respondents and obtained 167 respondents. The research instrument was a questionnaire with a 5-point Likert scale. The path analysis method and the Sobel test with the help of SPSS software were used to test the hypothesis. The results of this study indicate that human resource competence and organizational climate have a positive and significant effect on work motivation. Organizational climate and work motivation have a positive and significant effect on job satisfaction, while HR competencies do not have a significant effect on job satisfaction. Then work motivation can mediate the relationship between HR competencies on job satisfaction and the relationship between organizational climate and job satisfaction.